Answer:
(foh)(6) = -29
Step-by-step explanation:
(f o h)(6) is f(h(x)) when x = 6.
We have that:
f(x) = 4x - 1
h(x) = -x-1
f(h(x)) = 4(-x-1) - 1 = -4x - 4 - 1 = -4x - 5
(foh)(6) = -4(6) - 5 = -29
(foh)(6) = -29
Answer:
Step-by-step explanation:
it’s the last one
Answer:
$4/ hour
Step-by-step explanation:
every hour you go you add 4 dollars
example: 1 hour is $2
2 hours is $6
Answer: Hi there
To find the last term in order to obtain the perfect square, take the middle term, divide it by 2, and take its square.
10 ÷ 2 = 5
5^2 = 25
Thus, the equation would be x^2 + 10x + 25
The answer is 25
Maybe mark Brainliest
:D
Answer:
Hey!
Step-by-step explanation:
Your answer is 2409725.0
Best of luck ♥